Contribution to the clinical and histopathology of syphilitic endarteritis of the small vessels of the cortex - Encinas, E. (1943)
The histological changes of the brain and of the other organs of the patient who was admited to the Psycopathic Hospital de la Magdalena del Mar, has been studied. The patient was admited to the hospital thirty years ago with the diagnosis of Demencia Precox. The discharge diagnosis was Maniac Psychosis. The examination showed lesions of Luetic endoarteritis of the small vessels of the cortex, an entity which was first studied in 1903 by Nissl and Alzheimer. It has been demostrated alterations in the vessels, meninqes, ganglion cells, and gliotic elements of the brain, and structural changes of the other organs. The predominant changes in the meninges are of a chronic and acute character. The former are old "alterations together with vascular sclerosis. The latter are peri-vascular infiltrations of phagocitic wandering cells in which it is frequent to find dense el elements of angular contours with a very rare or no nuclear bodies. This same cells are Frequent in the infiltrations of other organs, such as the Iiver. The dominant character of the typical vascular injury is the proliferation of the adventicial and endothelial cells. It is not unusual, specially in the vessels of large caliber to find alterations of a degenerative nature in the middle layer; these being as a rule of and sclerotic or hialine nature. In these vessels it is quite frequent to find the presence of proliferative and degenerative changes in the intima. The same vascular injuries are found in other organs like the uterus, adrenals, liver etc. Sclerotic changes have been proved to exist in the uterus; calcic concretions and complete calcic occlusions have been found in the vessels of Gasserian ganglion and in the csorcid plexus: hialine degenerations in the media of many vessels of the brain, adrenals, ovary and uterus; and endothelial bridges in the vessels of the ovary are also present. All this shows that the vascular alteration was of a general character. There are two kinds of alterations in ganglion cells, some due to alterations in the vessels and in close relation with these: the necrotic perivascular alterations: others are independent and far related with them: the systematic changes. The exclusive les ion of the cells of the IIIth plate of the cortex (Fig. Nr. 14 and 15) belong to this class, as it is the loss of the Purkinje cells and the deep necrotic changes of nucleus dentatus of the cerebellum. The parts that have a general vulnerability have been intensly affected such as the Cornu Ammonis. Not only in its constitutive insulated elements but also in its architecture. showing considerable changes (Fig. Nr 50). There is evident necrosis of the cells of the spinal cord, specially of the nucleeus propius cornu enterioris and of the nucleus myorabdoticus leterelis, many of these elements. specially those of the first group have disapeared. It is interest to note that some of these changes have not shown relation with the correspondent clinical manifestations. At least until a few before the patient died there were no symptoms of cerebellum or of spinal cord involvement. In adition it must be noted that in the cerebellum there was alterations of basket fibers which gives a resembles with the heredo-cerebellar ataxia of which cerebellar modifications are seperated because the organ mantein the granular layer undemne. Cerebellum changes are common in the desease. It is known that syphilis in all its diferent forms involves large sections of the cerebellum, sometimes entire lobules. With the use of the silver stein of DEL RIO HORTEGA it has been possible to make it easily visible both in the regions of the cortex as well as in the medula oblongata and other formations the most interesant gliotic formations of the astrocytic type, specialy in the periphery of the capilars where the perivascular gliotic rings have been intensly developed. AIso nets of glia of the most complicated weaves and elements have been found in different regions of the nervus systern. The histological examination has confirmed the long believed suposition that the architectural glia of the cortex is heterogeneus and therefore different in its defensive reactions. It would be advisable to study this point both in the normal and patological state. Diferently to what happenes in the general paralysis or in the acute process of syphilis. the microglial reaction has been practical null. The astrocyts has been the prevaling element: this change seems to go with a chronic state of the disease. lt has been found in the dorsal surface of the medula oblongata bodies of the “corpora amilacea" and certain degenerated states of the ganglion cells of the nucleus magnocellularis fumculi posterioris, sustantia reticulatis grisea, nucleus ambigues and nucleus arcuatus, beside gliotic neurophagic nodes. In the ventricles an exudative and proliferative ependimitis has taken place and subependym gliotic elements have penetrated in the inside of the cavity mixing themselves with the morphologic elements of the exudate. At least in some places there is a complete destruction of the ependimary fences; such alterations have often been observed in diferent cases of siphilis. 0ther organs beside the brain have been submited to a close study to determinate its pathological changes in the malady. A large number of the vessels have shown the same alteration as those of the brain, that is adventitial and endotelial proliferation, and degenerated changes in the media of the vessels of medium size. Together with these alterations and as its result, necrosis and degenerations of various kinds have been found in other organs such as the degenerative changes of the parenchyma of the liver and spleen, and of the cells and fibers of the Gasserian ganglion depending these last ones, as it can be seen in the photographs of a calcifing process in the capillairies. It is observed in the liver the different fases of a conective peribiliar proliferation which tend to close the biliar duct, and the particular reaction of the Kuppffer cells. (Fig. N° 64). In the hypophysis, a great increase of the fibrous components, can be seen. Clinically the disease was of a chronic nature: its symptoms of a maniatic Psychosis. The inmediatly cause of death was heart failure; the most notable aspect from the psiquic point of view was the contribution presented by the patient hability to recite a remarkable number of songs of national folklore, old refrains which she was able to remember with extremly fidelity to the last.